Bebida alcohólica tipo vino a partir de la fermentación anaeróbica del mango Tommy Atknis (Mangifera indica L.) conel uso de dos edulcorantes. - Nieto Huacón, Willer Israel (2017)
In our country, the production of mango has been positioned among the pointers worldwide; Although more fixed in the export of certain varieties like Tommy Atkins and Kent, but without adding value with the transformation in some processed one; On the other hand, the elaboration of fruit wines is a little developed activity in the country, but that in the international scope is increasing. This research aimed to take advantage of the production of Tommy mango, where the idea arose of making a mango wine drink type Tommy Atkins with the application of two sweeteners, white sugar (e1) and honey (e2), applying variation in the dosages being these at 10 (d1), 20 (d2) and 30 % (d3). During fermentation treatments were evaluated every 24 hours, analyzing parameters of brix and pH; concluding at 13 days, when the values of °brix and pH were stabilized. Among the variables evaluated, the physicochemical composition was obtained, where favorable results were obtained for the sweetener "e1", as well as during the fermentation stage, and in the "d2" and "d3" dosages. The best data for the variables in relation to the treatments under study were: pH with 3.46 in T3 (e1d2), titratable acidity with 0.67 T5 (e1d3), brix with 8.4° T3 (e1d2), density with 1.0007 g/cm3 T2 (e2d1) and alcohol levels with 13° T5 (e1d3). In addition, a sensorial analysis was carried out to determine the best treatment (attribute liking) in the wine type drink, with 25 untrained tasters, evaluating attributes; showing the statistical analysis that the treatments T3 and T5 (white sugar at 20 and 30 %) after 20 days of fermentation, showed a superior acceptance by the panel of tasters, being the sweetness and the overall acceptance its main parameters of approval.